2009
DOI: 10.3892/or_00000588
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of PBMC obtained from leukapheresis products and tumor biopsies of patients with non-small cell lung cancer

Abstract: Abstract. The current study characterized peripheral blood mononuclear cells (PBMC) obtained from leukapheresis products of patients with non-small cell lung cancer (NSCLC) for cytokine release, the ability to incorporate tritiated thymidine following stimulation using PHA as well as the levels of both CD4 and CD8 regulatory T cells (Tregs) as defined by FoxP3 expression. Results were compared to normal donor PBMC obtained from buffy coat products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In humans, high numbers of CD4 + CD25 + Tregs were found in head and neck cancer [145], lung cancer [146, 147], pancreatic cancer [148], breast cancer [149], liver cancer [150], ovary cancer [151], and gastrointestinal cancer [152] either in the circulation or in the tumor itself. The appearance of Tregs at the tumor sites often correlates with poor prognosis of cancer patients [148, 151, 153, 154].…”
Section: Immunosuppressive Roles Of Foxp3+ Regulatory T Cells and mentioning
confidence: 99%
“…In humans, high numbers of CD4 + CD25 + Tregs were found in head and neck cancer [145], lung cancer [146, 147], pancreatic cancer [148], breast cancer [149], liver cancer [150], ovary cancer [151], and gastrointestinal cancer [152] either in the circulation or in the tumor itself. The appearance of Tregs at the tumor sites often correlates with poor prognosis of cancer patients [148, 151, 153, 154].…”
Section: Immunosuppressive Roles Of Foxp3+ Regulatory T Cells and mentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) are key cytokine-secreting immune cells, and their interactions with cancer cells may induce or suppress cancer-specific immune responses, including apoptosis induction and cytokine production, which contributing mostly to tumor progression [12], [21], [22]. Interactions between cancer cells and PBMCs occur in two main ways: through direct cell-to-cell contact, and through indirect cytokine-dependent mean.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported significantly higher percentage of CD4 + CD25 + FoxP3 + Treg in patients with advanced/metastatic NSCLC compared to healthy donors29303132, whereas the high percentage of CD152 + CD4 + CD25 high FoxP3 + Tregs correlates with more advanced stage of disease2933. Furthermore, two recent studies demonstrated a prognostic value of peripheral CD4 + FoxP3 + Treg in stage I-III NSCLC patients3435.…”
mentioning
confidence: 99%